Births of the O Menino Poeta [The Poet Boy] - Flávia Brocchetto Ramos; Marli Cristina Tasca Marangoni (Dialogos, 1970)
Access to literature in different periods and contexts imply different meanings , so that the copy of materiality requires natural modes of apprehension work.Thus, this study turns to the visualization of three different editions of d’O menino poeta [The poet boy], by Henriqueta Lisboa, aiming to shed some light on the contributions from the proposed typographic to the construction of meaning by the reader, which contemplates the different conceptions of childhood, of reading and of the underlying child reader.